Membrane Transporters for Bilirubin and Its Conjugates: A Systematic Review - Čvorović, Jovana; Passamonti, Sabina (Frontiers in Pharmacology, 2017)
Background Bilirubin is a highly-hydrophobic tetrapyrrole which binds to plasma albumin. It is conjugated in the liver to glucuronic acid, and the water-soluble glucuronides are excreted in urine and bile. The membrane transporters of bilirubin diglucuronide are well known. Still undefined are however the transporters performing the uptake of bilirubin from the blood into the liver, a process known to be fast and not rate-limited. The biological importance of this process may be appraised by considering that in normal adults 200-300 mg of bilirubin are produced daily, as a result of the physiologic turnover of haemoglobin and cellular cytochromes. Nevertheless, research in this field has yielded controversial and contradicting results. We have undertaken a systematic review of the literature, believing in its utility to improve the existing knowledge and promote further advancements. Methods We have sourced the PubMed database until 30 June 2017 by applying 5 sequential searches. Screening and eligibility criteria were applied to retain research articles reporting results obtained by using bilirubin molecules in membrane transport assays in vitro or by assessing serum bilirubin levels in in vivo experiments. Results We have identified 311 articles, retaining 44, reporting data on experimental models having 6 incremental increases of complexity (isolated proteins, membrane vesicles, cells, organ fragments, in vivo rodents, and human studies), demonstrating the function of 19 membrane transporters, encoded by either SLCO or ABC genes. Three other bilirubin transporters have no gene, though one, i.e. bilitranslocase, is annotated in the Transporter Classification Database. Conclusions This is the first review that has systematically examined the membrane transporters for bilirubin and its conjugates. Paradoxically, the remarkable advancements in the field of membrane transport of bilirubin have pointed to the elusive mechanism(s) enabling bilirubin to diffuse into the liver as if no cellular boundary existed.